Synthesis and characterization of aluminium substituted calcium hexaferrite - Shinde, V.S. (Heliyon, 2020)
Al substituted M type Ca hexaferrite with composition CaAl(x)Fe(12-x)O(19) (x = 0, 0.2, 0.4, 0.6, 0.8) were synthesized by sol gel auto combustion method. The prepared samples were characterized by XRD, SEM, FTIR and VSM. X ray diffraction study shows that the with increasing aluminum ion concentration lattice parameter a decreases from 5.87 [Formula: see text] to 5.83 [Formula: see text] while the lattice parameter c decreases from 22.15 Å to 22.00 Å are well within the range of M type of hexaferrite. The crystallite size of the particles decreases from 74.36nm to 62.12nm are suitable for magnetic recording. Morphology of the particles from SEM images was hexagonal platelet. The absorption band between 580 and 440cm(−1) in FTIR confirm the formation of hexaferrite. The magnetic properties of the samples changes with Al ion substitution make the material suitable for low density longitudinal and perpendicular magnetic recording.